Rationale of arthroscopic surgery of the temporomandibular joint - KenIchiro Murakami (Elsevier, 2013)
Arthroscopic surgery has been widely used for treatment of temporomandibular joint (TMJ) internal derangements and diseases for the last 40 years. Although 626 articles have been hit by Pubmed search in terms of "TMJ arthroscopic surgery", this review article is described based on distinguished publishing works and on my experiences with TMJ arthroscopic surgery and related research with an aim to analyse the rationale of arthroscopic surgeries of the temporomandibular joint.With arthrocentesis emerging as an alternative, less invasive, treatment for internal derangement with closed lock, the primary indication of arthroscopic surgery seems to be somewhat limited. However, the value of endoscopic inspection and surgery has its position for both patient and physician with its long-term reliable results.